Kearifan Lokal Masyarakat Nias dalam Mempertahankan Harmoni Sosial - Sri Suwartiningsih; David Samiyono (Societas Dei: Jurnal Agama dan Masyarakat, 2014)
Abstract:Being a pluralist community, Nias consists of not only the Nias ethnic group but also other ethnic groups, such as Tionghoa (Chinese), Padang, Batak and Javanese. Social harmony within the community is like no other ever found in other regions across Indonesia. Indeed, social harmony amongst the Nias community has been a very much interesting social fact for research and analysis. Has some sort of local wisdom been exercised as a social capital to create the social harmony within the life of this religious-pluralist community? A research on this was conducted in Kota Gunungsitoli by applying the descriptive-qualitative research. The research shows that their local wisdom of Banua dan fatalifus/em>ta, Emali dome si so ba lala, ono luo na so yomo, Sebua taideide sideideide mutayaig/em>and the fact that religious communites in this region have strong understanding and emphasize on their religious values are matters that heavily influence both the creation and the preservation of the social harmony within the community. Keyword :Social-harmony, Religious Pluralism, Cultural diversity, Nias, Banua dan fatalifus/em>ta